2006
DOI: 10.1097/00000542-200608000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Epidural Analgesia Augments Ileal Mucosal Capillary Perfusion and Improves Survival in Severe Acute Pancreatitis in Rats

Abstract: Thoracic epidural analgesia attenuated systemic response and improved survival in severe acute pancreatitis. These effects might be explained by improved mucosal perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 37 publications
1
37
1
1
Order By: Relevance
“…Recently, TEA has also been shown to ameliorate organ injury and improve outcome in sepsis, cardiovascular mortality and necrotizing pancreatitis (12)(13)(14). In the present study, it was hypothesized that TEA would increase liver blood fl ow due to the increase in splachnic perfusion and thus reduce the IR damage.…”
Section: Introductionmentioning
confidence: 86%
“…Recently, TEA has also been shown to ameliorate organ injury and improve outcome in sepsis, cardiovascular mortality and necrotizing pancreatitis (12)(13)(14). In the present study, it was hypothesized that TEA would increase liver blood fl ow due to the increase in splachnic perfusion and thus reduce the IR damage.…”
Section: Introductionmentioning
confidence: 86%
“…Animal models of acute pancreatitis treated with thoracic epidural blockade [13,16] , showed reduced histologic signs of pancreatic necrosis and a restoration of continuous capillary perfusion and arteriolar blood flow, moreover, survival rate was significantly higher in both of the studies. The microcirculatory effects induced by TEA could contribute in interrupting the ischemic injury involved in the beginning and progression of pan creatic lesions.…”
Section: Pancreatic Microcirculation and Acute Pancreatitismentioning
confidence: 92%
“…Freise et al [13] in a rodent model of acute pancreatitis, found a decrease in ileal mucosa interca pillary area, IL6 and lactate levels, in animals treated with both immediate or delayed epidural injection of local anesthetic. These results indicate that a thoracic epidural block improved local perfusion.…”
Section: Rabbits Hoganmentioning
confidence: 98%
See 2 more Smart Citations